Cenário ambiental da bacia hidrográfica do Arroio Grande a partir das diatomáceas epíliticas e fatores abióticos - Silva, Juliana Ferreira da (2014)
Activities carried on around aquatic systems are reflected in the water quality of these environments as well as in their biotic communities. Epilithic diatomsare known effective bioindicators.This study aimed to assess the environmental situation of the Arroio Grande Hydrographical Basin, RS, Brazil, situated in agricultural land and away from urban occupation. Monthly samplings of water and epilithic diatoms were carried out from October 2012 to March 2013 in thirteen sampling points. Permanent slides for the analysis of diatom communities were mounted andat least 600 valves per slide were counted to estimate the relative abundance. Taxa were identified to species level. Dissolved oxygen, conductivity, turbidity and water temperature were measured on site while pH, biochemical oxygen demand, alkalinity, hardness, nitrate, nitrite, phosphate and pesticides were analysed in the laboratory. 110 taxa belonging to 22 families and 39 genera were identified.The most representative families were Sellaphoraceae (20) followed by Naviculaceae (15) and Cymbellaceae (12). The sampling sites with higher species richness were the points on the west side of the basin. The richest genera were GomphonemaEhrenberg, Sellaphora Mereschkowskyand Navicula Bory. Diatom relative abundance and abiotic variables results were analysed by multivariate ordination and Anosim. The greatest variation was found among sampling months and a spatial gradient has not been identified.Althought water quality in the area was found to be good, the diatom community has responded to the various agricultural activities carried out along the sampling period.